A Survey on various Clustering Algorithms in Wireless Sensor Network - Singh, Karampal; Attri, Varinder (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless Sensor Network has gained the attention ofscientists and researchers because of its potential for applications invarious fields of science and technology and is one of the mostrapidly advancing technologies. Wireless sensor network faces somesevere resource and computational constraints due to which theirimplementation becomes a difficult task. Among the resourceconstraints, the major challenge for WSN is energy limitation.Energy efficient algorithms must be implemented so as to prolong thelifetime of network. Network lifetime can be maximized throughclustering algorithms, where cluster is responsible for sending thedata to the base station and not all the nodes are involved intransmission of data. In this paper, we summarized various clusteringalgorithms for WSNs and draw comparison between them based onclustering properties, cluster head capability and clustering processand briefly discuss types of clustering as well as discuss variousperformance metrics, challenges and issues faced during theformation of cluster head.